Continuous Infraclavicular Brachial Block Versus Single-Shot Nerve Block for Distal Radius Surgery: A Prospective Randomized Control Trial. Issue 1 (January 2018) - Ganta, Abhishek; Ding, David; Fisher, Nina; Lavery, Jessica; Jain, Sudheer; Tejwani, Nirmal C.
Abstract : Objectives: To compare the efficacy of an infraclavicular single-shot nerve block to a continuous infusion through an OnQ infusion pump for rebound pain (between 12 and 24 hours postoperatively) and postoperative narcotic analgesia requirements in distal radius fractures. Design: Prospective randomized control trial. Settings: Performed at 2 hospitals affiliated with a large urban academic medical center. Patients: Fifty patients undergoing operative fixation of distal radius fractures (OTA/AO type 23B/C). Intervention: Patients were randomized to receive either an infraclavicular block as a single shot (SSB group) or a continuous infusion through an OnQ pump (OnQ group). Main Outcome Measures: Visual analog scale (0–10) pain levels and amount of pain medication taken. Results: At all time points after discharge, mean postoperative pain scores were lower in the OnQ group versus the SSB group but did not reach statistical significance. At 12 hours postoperatively, the SSB group and OnQ group pain scores, respectively, were 5.2 and 4.1 ( P = 0.1615). At 24 hours, the pain scores for the SSB and OnQ group, respectively, were 5.4 and 4.8 ( P = 0.1918). At these same time points, the Percocet taken were the same at 1.3 and 2.3 ( P = 0.8328 and 0.8617). Overall 5 of 24 patients in the OnQ group had pump malfunctions with 4 being removed before 48 hours. Conclusion: OnQ pump is not associated with statistically improved postoperative pain control compared with a single nerve block for distal radius fractures and did not address rebound pain. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.